Effects of irrigation , type of fertilizer and nitrogen rate on yield components and total yield of mango (Mangifera indica L.) in Abu Karshoula, South Kordofan State, Sudan - Ewida, Sheikh Edin; Elkashif, Mohamed; Elamin, Osman (Gezira Journal of Agricultural Science, 2013)
An experiment was conducted at Abu Karshoula, South Kordofan State, Sudan, during the  seasons of 2009/10 and 2010/11, to determine the effects of irrigation, type of fertilizer and nitrogen rate on yield components and total yield of the local mango cultivar Kitchener. Treatments consisted of irrigated or non-irrigated trees. Types of fertilizer were urea, cow manure and a combination of urea and cow manure. Nitrogen rates were 0 kg/ha, 43 kg/ha and 86 kg/ha. The treatments were arranged in a split-split plot design with irrigation treatments as the main plots, type of fertilizer as the sub-plots and N rates as the sub-sub plots, replicated three times. Results showed that irrigation of mango trees significantly increased exportable yield, cull yield, number of fruits per tree and total yield, whereas, withholding irrigation from mango trees gave higher locally marketable and lower cull yields in both seasons. Nitrogen fertilizer in the form of urea produced the largest number of fruits per tree and the highest locally marketable  and total yields in both seasons. Combination of urea and cow manure significantly increased exportable yield in both seasons. However, nitrogen fertilizer in the form of cow manure  alone gave the lowest total yield and number of fruits per tree in both seasons. Application of N at the rate of 86 kg/ha coupled with irrigation significantly increased number of fruits per tree, cull, exportable and total yields.  Hence, it is recommended to irrigate mango trees and apply N in a combination of urea and cow manure at the rate of 86 kg/ha in order to increase total and exportable yields. أجريت التجربة بأبي كرشولا، ولاية جنوب كردفان, السودان لموسمي 2009/10و2010/11 لمعرفة تأثير الري ونوع السماد ومعدل النتروجين على مكونات الإنتاج و الإنتاج الكلي لصنف المانجو المحلي كتشنر.اشتملت المعاملات علي ري أشجار المانجو أو عدم ريها. مصادر النتروجين كانت يوريا و روث الأبقار و خليط من اليوريا و روث الأبقار. إضيف النتروجين بمعدلات صفر و43 و86 كجم N/هكتار. صممت التجربة بطريقة القطع المنشقه مرتين . كانت معاملة الري هي القطعة الرئيسيه ونوع السماد هي القطعه المنشقه ومعدل النتروجبن هو القطعه المنشقه المنشقه وتم تكرارها ثلاث مرات. أظهرت النتائج أن ري أشجار المانجو أدى إلى زيادة معنوية في إنتاج مانجو الصادر و الثمار المخدوشه وعدد الثمار للشجره و الإنتاج الكلي.  بينما ادى حجب الماء عن أشجار المانجوالى أعلى إنتاج للسوق المحلي و أقل ثمار مخدوشه.ادى سماد اليوريا الى أعلى عدد من ثمارالمانجو للشجره و أعلى إنتاج للسوق المحلي وأعلى إنتاج كلي في الموسمين.كما ادى خلط اليوريا و ماروق روث الأبقاربنسبة 50% لكل إلى زيادة معنوية في إنتاج الصادر في الموسمين. بينما اعطى سماد ماروق روث الابقار أقل إنتاج كلي و عدد الثمار للشجرة في الموسمين .ادت إضافة السماد إلى زيادة معنوية فى  عدد الثمار للشجره و إنتاج الصادر و الإنتاج الكلي في الموسمين بينما ادى معدل86 كجم N/هكتارالى أعلى إنتاج لمانجو  الصادر و إنتاج كلي في الموسمين مقارنة بمعدل 43 كجم N/هكتار. توصى الدراسة بري أشجار المانجو وإضافة النتروجين في شكل خليط من اليوريا وماروق روث الأبقار بمعدل 86 كيلوجرام N /هكتار لزيادة الإنتاج الكلي وإنتاج الصادر.